1989
DOI: 10.1093/bja/63.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia-Induced Respiratory Depression: Comparison of Meptazinol and Morphine in the Postoperative Period

Abstract: Forty-nine patients undergoing elective total hip replacement received either morphine or meptazinol for postoperative analgesia from a patient-controlled analgesia apparatus. Ventilatory rate and volume and arterial oxyhaemoglobin saturation were recorded continuously for the first 24 h following surgery. Episodic hypoxaemia was seen in both groups, associated with disturbances in ventilatory pattern. There was no significant difference in the incidence or severity of observed hypoxia between the groups, or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…During the inpatient stay, pain scores during 8-hour intervals, narcotic use, and physical therapy milestones were compared. Results With the numbers available, we detected no clinically important difference in pain scores throughout the hospital stay; however, patients treated with liposomal bupivacaine consumed very slightly less narcotics overall (96 ± 62 versus 84 ± 73 eq mg of morphine; [95% confidence interval, [11][12][13] Each author certifies that his or her institution approved the human protocol for this investigation, that all investigations were conducted in conformity with ethical principles of research, and that informed consent for participation in the study was obtained. One of the authors (RI) received a grant and personal fees from Pacira Pharmaceuticals (Parsippany, NJ, USA).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…During the inpatient stay, pain scores during 8-hour intervals, narcotic use, and physical therapy milestones were compared. Results With the numbers available, we detected no clinically important difference in pain scores throughout the hospital stay; however, patients treated with liposomal bupivacaine consumed very slightly less narcotics overall (96 ± 62 versus 84 ± 73 eq mg of morphine; [95% confidence interval, [11][12][13] Each author certifies that his or her institution approved the human protocol for this investigation, that all investigations were conducted in conformity with ethical principles of research, and that informed consent for participation in the study was obtained. One of the authors (RI) received a grant and personal fees from Pacira Pharmaceuticals (Parsippany, NJ, USA).…”
Section: Introductionmentioning
confidence: 90%
“…The traditional approaches, pairing opioid patient-controlled analgesia with oral narcotics and the use of peripheral nerve blocks, have been shown to be effective in controlling pain [19]. Despite the effectiveness of narcotics, these agents are associated with side effects such as respiratory depression, hypotension, urinary retention, and postoperative ileus [11,25]. Additionally, peripheral motor nerve blocks are associated with specific complications, including increased fall risk as a result of quadriceps weakness, potential injury to the nerve itself as well as increased resource utilization and total costs of care [10].…”
Section: Introductionmentioning
confidence: 99%
“…A fuller description of the technique of analysis can be found in a previous paper (Frater et al, 1989 Table 1 also shows the duration of sleep on each recording night for the two groups. There was no significant difference in the mean duration of sleep between the two groups on any night.…”
Section: Normal Respiration (Nr)mentioning
confidence: 99%
“…It has been demonstrated that the incidence of arrhythmias is as great in the postoperative period as during the operation [31]. Arrhythmias commonly accompany OSA which has been shown to occur in the postoperative period even in apparently asymptomatic subjects [24].…”
Section: Recoverymentioning
confidence: 99%